(untitled) (Homoeopathy for All, 2023)
Atopic eczema (dermatitis), a type of eczema, is a chronic inflammatory skin disease posing a significant burden on health care resources. It affects up to 3% of adults; recent data show that its prevalence is still increasing, especially in low socio economic countries. There is limited evidence to support the use of conventional treatment of this condition. With reference to the current scenario prevalence of atopic dermatitis in adults is increasing. Homoeopathy treats the individual in disease and not the disease alone and holistically helps the patient in need. Thus by striking at the root of the problem patient can be relieved from further remission of suffering.